A computer-assisted proof for solutions of Elkouh’s equation related to Navier–Stokes equations - Yoshitaka Watanabe; Shuting Cai (Fixed Point Theory and Algorithms for Sciences and Engineering)
Abstract The present paper presents a computer-assisted proof of the existence of solutions for Elkouh’s equation, which is representative of fluid flow between parallel circular disks. The proposed approach is based on an infinite-dimensional fixed-point theorem with interval arithmetic. Various existing proofs with mathematically rigorous error bounds show the validity of the presented numerical verification method.